PENGARUH MODIFIKASI PERMAINAN BOLAVOLI TERHADAP MOTIVASI SISWA DALAM PEMBELAJARANÂ PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN ( STUDI PADA KELAS VIII SMP NEGERI 2 SUKOREJO, PONOROGO ) - YUNIANSYAH, FEBRI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Learning Sport and Physical Health Education will not go hand in hand if there’s lack of a balanced interaction between teachers and students. Just like as learning volleyball, will not run smoothly if students do not perform tasks given by the teacher with a passion. That's because the monotone learning method. To give the injection of spirit a teacher should be able to make learning interesting and not monotonous, because the monotony of learning will make students  bored and lazy to interact so that learning objectives may not be delivered. One method is to enable students to be motivated is to modify the volleyball game, as well as good facilities and infrastructure used in the lesson. The purpose of this study is to determine the effect of modified volleyball game to student motivation in learning procees sport and physical health education in eighth grade SMP Negeri 2 Sukorejo, Ponorogo, and how much influence. This research is descriptive quantitative experimental approach. The subjects in this study amounted to 56 students, consisting of 28 students of class VIIIA as the experimental group and 28 students of class VIIIC as a control group. Sampling technique using random cluster sampling. The instrument used was a questionnaire motivation of students. for data analysis using the t test (independent). Based on the calculation can be concluded that there is a significant effect of modificatied volleyball game to students motivation in learning procees sport and physical health education  in eighth grade students of SMP Negeri 2 Sukorejo, Ponorogo as evidenced from the results tcount 2.431 > ttable 2,021 with significance level 0,05. The influence is as big as 11,93%. Keywords: Modification of volleyball game, Student Motivation, Learning Sport and physical health education